Liver fibrosis scores and risk of liver‐related mortality in young adults with chronic hepatitis B: A cohort study. Issue 1 (7th October 2021) - Sohn, Won; Chang, Yoosoo; Cho, Yong Kyun; Hong, Yun Soo; Shin, Hocheol; Ryu, Seungho
Abstract: The predictive role of noninvasive liver fibrosis scores on liver‐related mortality in patients with chronic hepatitis B below 40 years of age remains unclarified. We examined the association of liver fibrosis scores with liver‐related mortality in young (<40 years) and older adults with hepatitis B virus (HBV) infection. A cohort study was performed in 21, 360 HBsAg‐positive Korean adults without liver cirrhosis or liver cancer at baseline who were followed up for up to 18 years. The liver fibrosis scores were determined using the fibrosis‐4 score (FIB‐4) and aspartate transaminase to platelet ratio index (APRI). Patients' vital status and cause of death were ascertained through the National Death Records. During a median follow‐up of 10.2 years, 283 liver‐related deaths were identified (liver‐related mortality, 127.4/10 5 person‐years). The liver fibrosis scores were significantly associated with increased risks of liver‐related mortality; this association did not differ by age group (<40 vs. ≥40 years). The multivariable‐adjusted hazard ratios with 95% confidence intervals for liver‐related mortality comparing intermediate and high to low FIB‐4 scores were 4.23 (1.99–9.00), and 15.16 (5.18–44.38), respectively, among individuals under 40, and 4.46 (3.03–6.56) and 22.47 (15.11–33.41), respectively, among older individuals. These associations were similar in analyses using APRI. In this cohort of HBsAg‐positive individuals, the liver fibrosis scores were associated with increased risks of liver‐related mortality in young and older adults. The liver fibrosis scores have a role in predicting liver mortality, even in young adults with HBV.